Lone-parent incomes and work incentives - Mark Regan; Claire Keane; John Walsh (The Economic and Social Research Institute (ESRI), 2018)
This paper examines how changes to the social welfare system for lone parents, such as the tightening of eligibility criteria for One-Parent Family Payment and the introduction of Jobseeker's Transitional Payment, affected lone-parent incomes and work incentives. Our main contributions are threefold: we examine the cumulative effect of policy changes on the income of lone parents, and how changes to lone-parent-specific schemes affected income and work incentives, and quantify the extent to which childcare costs act as a labour market barrier for lone parents. Firstly, policy changes do not occur in a vacuum, therefore we assess how all policy from 2011 to 2018 a ffected lone-parent income. We find that changes to social welfare policy for lone parents resulted in income losses for employed lone parents, but had little effect on non-employed lone parents. All other changes over the period decreased the income of both employed and non-employed lone parents. We examine how these social welfare changes affected the work incentives . The reforms resulted in mor e lone parents having a greater financial incentive to be out of work, thus weakening the financial incentive to be in work. Finally, informed by an abundant literature regarding childcare costs as an obstacle to female labour supply, we highlight the impact of these costs on the incentive to be in work. We find that on accounting for childcare costs, being out of work becomes much more financially attractive for many lone parents. The availability of subsidies on childcare costs helps to reduce this disincentive, but even so, childcare costs represent a substantial barrier to lone-parent labour market participation.
Keywords: 330